Impact of bubble size on the integral characteristics of bubble plumes in quiescent and unstratified water. (April 2020) - Li, Geng; Wang, Binbin; Wu, Huijie; DiMarco, Steven F.
Highlights: Bubble sizes and population have strong impacts on velocity, width, and fluxes of volume and momentum in bubble plumes. Bubble impacts are attributed to different mechanisms of energy and momentum transport in the flow. Integral model is a valid tool to characterize the bubble plume for different bubble sizes and population. Abstract: We present an experimental study to investigate the impact of bubble size on behavior of bubble plumes from the integral point of view. Two distinct types of bubble plume were generated under the same volumetric gas flow rate: many small bubbles using an air-stone diffuser and a few large bubbles using a single-orifice diffuser. Using Particle Image Velocimetry, we measured the velocity field in the plumes, and derived the integral characteristics for comparison, including the evolution of plume width, centerline velocity, volume flux, momentum flux, momentum amplification factor, and the entrainment coefficient. The measurement data show that the evolution of all the parameters in the plumes are influenced strongly by the different bubble sizes and population. The plumes with many small bubbles behave closer to the single-phase coherent plumes, showing a linear growth of plume width and a decreasing centerline velocity. These characteristics are modified in the plumes with fewer but larger bubbles. With the same total initial buoyancy flux from the source, fewer but larger bubbles give rise to weaker mean flow characteristics, i.e., smaller plume velocity and weaker fluxes of volume and momentum. This modification is attributed to the different mechanisms in fundamental transport of energy and momentum between mean and fluctuating components. In the single-orifice cases, the plumes are influenced by stronger but less frequent bubble wakes, compared to those more coherent bubble plumes in the air-stone cases. Higher momentum amplification factors were found in bubble plumes with fewer but larger bubbles, indicating a stronger ratio of turbulence to mean in these plumes. Despite the modification, all bubble plumes support a typical shear entrainment process within 40 cm height-of-rise. Hence, the integral model and the universal scaling using the plume length scale D and the bubble slip velocity Ws were found to describe the integral behavior of bubble plumes generally well in the range of our experimental parameters, regardless of the different bubble sizes and population.